A Micrometer‐Sized Silicon/Carbon Composite Anode Synthesized by Impregnation of Petroleum Pitch in Nanoporous Silicon. Issue 40 (16th August 2021) - Chae, Sujong; Xu, Yaobin; Yi, Ran; Lim, Hyung‐Seok; Velickovic, Dusan; Li, Xiaolin; Li, Qiuyan; Wang, Chongmin; Zhang, Ji‐Guang
Abstract: Porous silicon (Si)/carbon nanocomposites have been extensively explored as a promising anode material for high‐energy lithium (Li)‐ion batteries (LIBs). However, shrinking of the pores and sintering of Si in the nanoporous structure during fabrication often diminishes the full benefits of nanoporous Si. Herein, a scalable method is reported to preserve the porous Si nanostructure by impregnating petroleum pitch inside of porous Si before high‐temperature treatment. The resulting micrometer‐sized Si/C composite maintains a desired porosity to accommodate large volume change and high conductivity to facilitate charge transfer. It also forms a stable surface coating that limits the penetration of electrolyte into nanoporous Si and minimizes the side reaction between electrolyte and Si during cycling and storage. A Si‐based anode with 80% of pitch‐derived carbon/nanoporous Si enables very stable cycling of a Si||Li(Ni0.5Co0.2Mn0.3)O2 (NMC532) battery (80% capacity retention after 450 cycles). It also leads to low swelling in both particle and electrode levels required for the next generation of high‐energy LIBs. The process also can be used to preserve the porous structure of other nanoporous materials that need to be treated at high temperatures. Abstract : A micrometer‐sized silicon/carbon composite anode developed by facile and scalable impregnation of petroleum pitch that stabilizes nanoporous Si against sintering at high temperature is reported. The composite anode including single nanometer‐sized primary particles shielded by pitch‐derived carbon exhibits outstanding battery performance such as 80% capacity retention after 450 cycles in the full cell system.